Intersections of Forced Migration and Gender in Physical Education - Bartsch, Fabienne; Rulofs, Bettina (Frontiers in Sociology, 2020)
Rising refugee movements have affected global society in general and the social system of sports in particular. The main structures and discourses of the sports system are also reflected in physical education (PE) at schools, which can, therefore, be regarded as an integral part of it. PE can play a significant role in the sports biographies of young people from refugee backgrounds. It is the only organizational framework of sports that all children and adolescents experience, and for many young people from refugee backgrounds it is the first and sometimes the only context in which they come into contact with sports in the host country. Consequently, PE teachers have a special opportunity to support students from refugee backgrounds in discovering their sports-related interests and to encourage them to deepen these interests outside school. Research suggests that teachers interact with learners from refugee backgrounds with stereotypical expectations for how they should behave and act. These expectations are structured along gender-specific logics, with male persons from refugee backgrounds often being classified as violent and threatening and female individuals from refugee backgrounds as fragile and oppressed. Against this background, through an interview study with 31 PE teachers from schools in Germany, we investigate teachers' perspectives on young people from refugee backgrounds. Specifically, we examine which intertwined gendered and racialized patterns of perception and interpretation become apparent when PE teachers talk about this group of students. Constructivist, intersectional, and postcolonial approaches are used to analyze the interviews and answer the research questions. The analytical screening of the interviews reveals that gendered and racialized perceptions of threat and vulnerability dominate the teachers' mindsets. Four main patterns that follow these gendered and racialized thoughts can be detected in the data material: victimization and vulnerabilization, notions of threat and impulsivity, claims for assimilation and normalization, and demands for discipline. These perceptions can influence the developmental opportunities of students from refugee backgrounds and reduce their participation and involvement in school sports and out-of-school sports contexts. Based on these results, we discuss strategies that might support (future) teachers in breaking stereotypes and overcoming narrow perceptions of young people from refugee backgrounds.